Unstated Rage and Undefined Identity in Anna Burns’ Milkman: A Feminist Post-Structuralist Reading - Md Mozaffor Hossain (LET: Linguistics, Literature and English Teaching Journal)
Northern Irish author, Anna Burns’ Man Booker Prize (2018) winning novel Milkman presents a narrative textured with multifarious considerations ranging from subjectivity, gender, politics, power, language, and religion to anything a reader may logically connect it with. One of its most noticeable features is the narrator’s not explicitly stating the unspeakable rage searing herself and the society as a whole, which is obvious in the syntactic, lexical, intonational and tonal treatments, and her not clearly revealing the identities of the characters. Researcher regard these aspects of the narrative open to myriad interpretations of which I would like to use the feminist post-structuralist view to fathom the novel in its profoundness. I intend to unravel the stereotyped gender and subjectivity features of feminist poststructuralism in the novel, which hinge upon the social mechanism, lived experiences, and language and power relations both directly and indirectly portrayed in the narrative.